Use of MM5 model for weather forecasting over Bangladesh region - Akter, Nasreen; Islam, Md. Nazrul (BRAC University, 2010)
The severity of weather appears almost every year in Bangladesh. It causes damage of property and takes a very high death toll due to absence of timely and proper forecasting facility. Thus the focus of this paper is to demonstrate the usefulness of weather model for forecasting and estimating convective system. A high resolution mesoscale model MM5 has been used in this regard to observe the accurate rainfall estimation over Bangladesh. The model is run at two nested domains at 45 km and 15 km resolutions for two durations i.e. 31 March to 05 April 2002 and 20 to 25 May 2002. In both the cases, results indicate that the MM5 model has a good capability to estimate rainfall over Bangladesh